Newly Developed Semi-Solid Formulations Containing Mellilotus officinalis Extract: Characterization, Assessment of Stability, Safety, and Anti-Inflammatory Activity - Jovana Bradic; Anica Petrovic; Milos Nikolic; Nikola Nedeljkovic; Marijana Andjic; Nebojsa Kladar; Stefani Bolevich; Vladimir Jakovljevic; Aleksandar Kocovic (MDPI AG, 2024)
Melilotus officinalis has been traditionally used as an anti-inflammatory agent; nevertheless, a comprehensive evaluation of its efficacy and safety and comparison with standard drugs are lacking. Taking into consideration concerns with current therapies, like efficacy limitations, side effects, and resistance, we aimed to develop a natural gel and cream based on Melilotus officinalis extract and explore their anti-inflammatory potential. After the chemical analysis of the extract confirmed the presence of coumarin, p-coumaric acid, gallic acid, and quercetin, formulations were prepared and subjected to physical and chemical stability evaluations over 6 months. The safety potential was tested in rats, while the anti-inflammatory activity was assessed both via in silico tests and in a rat model of inflammation. The examined formulations showed stable physical characteristics at the defined storage conditions and did not exert any sign of adverse skin reaction. The gel formulation exhibited a remarkable effect in inflammation reduction comparable with hydrocortisone. The in silico results suggest that coumarin, p-coumaric, and gallic acid bind to COX-1 and COX-2 with a lower affinity compared to diclofenac. On the other hand, quercetin demonstrated comparable inhibitory activity and stronger interaction compared to the control drug. Our results indicate that the examined formulations are stable and safe and may be promising dermal products for the alleviation of inflammatory skin conditions.